Actinobacterial community dominated by a distinct clade in acidic soil of a waterlogged deciduous forest - Kopecký, Jan; Kyselková, Martina; Omelka, Marek; Čermák, Ladislav; Novotná, Jitka; Grundmann, Genevieve L; Moënne-Loccoz, Yvan; Ságová-Marečková, Markéta (FEMS microbiology ecology, 2011)
Members of the Actinobacteria are among the most important litter decomposers in soil. The site of a waterlogged deciduous forest with acidic soil was explored for actinobacteria because seasonality of litter inputs, temperature, and precipitation provided contrasting environmental conditions, particularly variation of organic matter quantity and quality. We hypothesized that these factors, which are known to influence decomposition, were also likely to affect actinobacterial community composition. The relationship between the actinobacterial community, soil moisture and organic matter content was assessed in two soil horizons in the summer and winter seasons using a 16S rRNA taxonomic microarray and cloning-sequencing of 16S rRNA genes. Both approaches showed that the community differed significantly between horizons and seasons, paralleling the changes in soil moisture and organic matter content. The microarray analysis further indicated that the actinobacterial community of the upper horizon was characterized by high incidence of the genus Mycobacterium. In both horizons and seasons, the actinobacterial clone libraries were dominated (by 80%) by sequences of a separate clade sharing an ancestral node with Streptosporangineae. This relatedness is supported also by some common adaptations, for example, to soil acidity and periodic oxygen deprivation or dryness.
Keywords: půda; Climate; roční období; podnebí; půdní mikrobiologie; Soil Microbiology; Molecular Sequence Data; stromy; Seasons; Trees; Actinobacteria; Base Sequence; Soil; koncentrace vodíkových iontů; Hydrogen-Ion Concentration; molekulární sekvence - údaje; sekvence nukleotidů